Styl życia a świadomość ekologiczna konsumentów na rynku turystycznym - relacje, uwarunkowania i problemy - Niezgoda, Agnieszka; Markiewicz, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Ecological awareness and the resulting ecological behaviors during the tourist trip are important issues for the future of resources and absorption of the tourism market. Authors put up a thesis that ecological awareness can be related with the way of life and the ways of consumption, but pro-ecological activities can also be the result of short-lived fashion. The aim of the article is to analyze the relationship between ecological awareness, lifestyle and real consumer behavior in the tourist market. The author presents the authoritative division of environmental factors of consumer behavior in the tourist market: personal, social (conformist) and ideological conditions. According to the suggestions presented in the Report from the analysis of awareness, attitudes and ecological behavior of Poles conducted in Poland in 2009–2015 for the Ministry of the Environment, qualitative research in the form of focused group interviews was used for empirical verification of relations between ecological awareness and tourists’ activities. It was noted that young people represent a high level of ecological awareness and understand the need to care for natural resources. However, behaviors are primarily influenced by social (conformist) conditions, which result from the acceptance of processes and phenomena that are happening in modern society: fashion for ecology, mandatory regulations, the desire to save money, etc. But youth also presents ecological behaviors that are the result of deep concern for the future. In order for ecological education to be effective and an integral part of the lifestyle, awareness of nature conservation should translate into real action. This is possible if the basic behavioral determinants are those described in this article as ideological as opposed to personal and conformist
Keywords: świadomość ekologiczna; konsumenci